Retrorectal epidermal cyst: report of four cases and review of the literature - Alver, Olcay; Paksoy, Melih; Baca, Bilgi; Erenler, İlknur and Kayabaşı, Bayram and Ayan, Fadıl and Dervişoğlu, Sergülen (Cerrahpaşa Medical Journal, 2013)
Objectives: Lesions occuring in the retrorectal space are rare and are derived from a variety of embryologic origins. Retrorectal cysts are one of the groups of these lesions. In this study, we presented four patients who had developmental retrorectal cysts and we also reviewed the literature. Methods: Patients who underwent surgical intervention for retrorectal cysts were included in this study. Medical records, results of digital and proctoscopic examination, endorectal ultrasonography, computarized tomography, magnetic resonance imaging and histopathological reports were reviewed retrospectively. Results: Four female patients underwent surgical resection of their retrorectal cysts. All of them were complaining of sense of fullness in the rectum, tenesmus, and dyspareunia. The posterior perineal route was used in all four patients. Mean postoperative stay was 7 (6-8) days. Mean follow-up time was 7 (3-13) years. Histopathological examination of resected specimens revealed epidermal cyst. All patients were discharged without any problem and during long term follow up, no recurrence or discomfort was encountered. Conclusion: Various imaging modalities have been used for the diagnosis and surgical treatment planning of retrorectal epidermoid cysts. We recommend complete surgical resection of these benign lesions.